DAMPAK SOSIAL EKONOMI PEMBANGUNAN DI KAWASAN SERIBU RUMAH GADANG BAGI MASYARAKAT NAGARI KOTO BARU KABUPATEN SOLOK SELATAN - Susiyanti Meilina; Roni Russandi (Ensiklopedia of Journal, 2021)
Sungai Pagu, South Solok Regency, became a world cultural heritage to the Organization. The cultural heritage in the area of a thousand rumah gadang is a symbol of tourism in the South Solok area, according to the Acting Regent of South Solok, Drs. H. Abdul Rahman, S.H., M.H. This uniqueness must be used as best as possible to improve the community's economy, and it must be used as best as possible to generate Regional Original Income (PAD) for the region and increase the community's economy while reducing unemployment and creating job opportunities. The objectives of this study are: 1) To determine the socio-economic impact of development in the area of a thousand rumah gadang for the Nagari Koto Baru community, South Solok Regency; 2) To find out what are the inhibiting factors in the socio-economic development in the area of a thousand rumah gadang for the Nagari Koto Baru community, South Solok Regency; 3) To find out what are the efforts made to overcome the socio-economic constraints of development in the area of a thousand rumah gadang for the Nagari Koto Baru community, South Solok Regency. This type of research is qualitative research. "Qualitative research is research that produces descriptive data in the form of written or spoken words from people or observed behavior." Selection of informants in this study were key informants. ; namely those who really understand the socio-economic impact of the development of the area of a thousand rumah gadang for the people of Nagari Koto Baru, South Solok Regency, who are the key informants of this research are: community leaders, community. Meanwhile, non-key informants: namely people who are considered to know the problem, namely some tourism office employees. The types of data are primary data and secondary data collected through interviews, observation and library research. The analysis technique used is qualitative analysis. The results of this study indicate that: the utilization of the rumah gadang is one of the efforts to preserve and protect the house from destruction. Not only get benefits from an economic and social perspective, the use of the rumah gadang as lodging is also an effort to protect and preserve it. However, in the development of the rumah gadang as an inn, the owner and local government should not remove the information content and its original form. The conclusion that can be drawn is the uniqueness of the rumah gadang which is located close to each other in one area in the Saribu Rumah Gadang area is one of the most favored by tourists when visiting South Solok Regency, West Sumatra. The tourist destination of Rumah Gadang Panjang in Abai, South Solok Regency, West Sumatra was nominated for the 2018 Anugerah Pesona Indonesia (API) category of the 10 most popular historical sites in Indonesia. The Saribu Rumah Gadang area has been included in the tourism development area in the district which was expanded in 2004 from Solok district. It has been included in the South Solok RTRW. The potential for cultural tourism is currently being developed and promoted by the local government together with tourism observers and actors. Suggestions include the development of tourism infrastructure and supporting facilities for tourists by involving cross-sectoral roles in the area, this can be improved through several activities, namely (1) providing an understanding of tourism development regulations; (2) increased involvement of community participation (3) involvement of tourism business actors; (4) Planning a concept.